Urgent-start peritoneal dialysis: is it ready for prime time?. Issue 6 (November 2019) - Tunbridge, Matthew; Cho, Yeoungjee; Johnson, David W.
Abstract : Purpose of review: This review aims to provide an up-to-date summary of the definition, current practice and evidence regarding the role of urgent-start peritoneal dialysis (USPD) in patients with end-stage kidney disease who present with unplanned dialysis requirement without functional access. Recent findings: USPD can be broadly defined as peritoneal dialysis initiation within the first 2 weeks after catheter insertion. Published practice patterns, in terms of catheter insertion approach, peritoneal dialysis initiation time or initial fill volume, are highly variable. Most evidence comes from small, retrospective, single-center observational studies and only one randomized controlled trial. Compared with conventional-start peritoneal dialysis, USPD appears to moderately increase the risk of mechanical complications, such as dialysate leak (relative risk 3.21, 95% confidence interval 1.73–5.95), but does not appear to adversely affect technique or patient survival. USPD may also reduce the risk of bacteremia compared with urgent-start hemodialysis delivered by central venous catheter (CVC). Summary: USPD represents an important opportunity to establish patients with urgent, unplanned dialysis requirements on a cost-effective, home-based dialysis modality with lower serious infection risks than the alternative option of hemodialysis via CVC. Robust, well executed trials are required to better inform optimal practice and safeguard patient-centered and patient-reported outcomes.